Factors associated to thermotolerant Campylobacter spp. contamination of broilers in three levels of the poultry chain for human consumption in Costa Rica (Ciencias Veterinarias, 2017)
Campylobacter spp. are bacteria known to cause foodborne diseases in both developed and developing countries. A cross-sectional study was conducted between March and July 2015 to determine the national prevalence of Campylobacter spp. in broilers for human consumption.  A simultaneous sampling design was used in three levels of the Costa Rican poultry production chain: 152 farm samples (CC), 104 plant samples (CA) and 96 retail store samples (PV). For this research, questionnaires were prepared with variables related to plant (CC and CA) and PV management. The plant questionnaire included variables related to general data such as location and volume of production, good hygiene and manufacturing practices (GHMP), as well as processes and HACCP. In PV aspects such as the following were evaluated: GHMP, product temperature, and price per kg/chicken. The following were identified as risk factors: resting period of live animals in platform > 60 minutes (PR = 2.28, 95% CI 1.23-4.21), processing speed